AN INTERVENTION-RESEARCH DEVICE WITH POSTGRADUATE THESIS DIRECTORS IN THE FACULTIES OF EDUCATION SCIENCES AND COMMUNICATION SCIENCES OF THE UNIVERSITY OF MALAGA, FROM A DOCTORAL PEDAGOGY - Viviana Mancovsky (Universidad Nacional del Nordeste, 2016)
This article aims to relate an experience of working with directors of postgraduate thesis (especially from the doctoral level) from an intervention-research device that was carried out in the Doctoral Program in Education and Communication of the Faculties of Sciences of The Education and Communication Sciences of the University of Málaga (Spain). It was accomplished in the framework of an invitation proposed by Dr. Nieves Blanco, program coordinator, in November 2015. This device recovers the theoretical contributions of a research line, initiated in 2008, centered on a Doctorate Pedagogy. The idea allowed to recover the voices of the directors who are encouraged to question and "ask themselves" about: what their task consists of, what they have to "give", what their motivations to lead are, what expectations on the work they perform they have, and the feelings that arise through the accompaniment. Likewise, it showed the richness thinking in a structured way the construction and implementation of intervention devices and the ever transient knowledge. Likewise, the richness of thought showed in a structured way the construction and implementation of intervention devices and the ever transient knowledge, in the making of an investigation.